European Cases in Strategic Management - edited by John Hendry (Chapman & Hall, 1993)
This collection contains 21 case studies in strategic management written and developed at Europe's leading business schools. All cases have been written in the last five years and refined through class-teaching and reviewing. Discussion questions and further reading accompany each case. The cases focus on companies from across Europe, including Poland, Hungary and Yugoslavia in addition to the dominant Western European economies. Most have a significant international dimension and address current issues such as global competition and European integration. They explore a variety of situations from giant multinationals down to small businesses, across a wide range of business sectors, and address all the major themes and issues in strategic management in Europe today. This book should be of interest to students at any level (HND, BABS, DMS, MBA, executive/professional) taking courses in strategic management. An ELBS/LPBB edition is available